A clinical study comparing BIVAP saline vaporization of the prostate with bipolar TURP: Early complications, physiological changes and postoperative follow-up outcomes - Aydogdu, Ozgu; Karakose, Ayhan; Atesci, Yusuf Ziya (Canadian Urological Association Journal, 2014)
Introduction: We compare BIVAP saline vaporization of the prostate with bipolar transurethral resection of the prostate (TURP) in the treatment of benign prostatic hyperplasia. Methods: In total, we included 86 patients treated with BIVAP (n = 44) and bipolar TURP (n = 42). The inclusion criteria were maximum urinary flow rate (Qmax) ≤10 mL/s, International Prostate Symptom Score (IPSS) ≥16, and prostate volume measured with transrectal ultrasound scan between 30 and 80 mL. Serum electrolyte, hemoglobin, and hematocrit levels were determined preoperatively and postoperatively. All patients were evaluated at the postoperative first and third months and the IPSS score, post-void residual urinary volume (PVR), Qmax, and average urinary flow rate (Qave) were compared. Statistical analyses were performed using SPSS 16.0 program and statistical significance was set at p < 0.05. Results: Preoperative demographic characteristics were similar in the 2 groups. The mean operation time was significantly higher (p = 0.02) and hospitalization time was significantly lower (p = 0.04) in the BIVAP group when compared to the bipolar TURP group. There was no significant difference between 2 groups in terms of preoperative and postoperative serum electrolyte, hemoglobin and hematocrit levels. Postoperative complication rates were similar in the 2 groups. The only exception was the rate of severe dysuria, which was significantly higher in the BIVAP group. No statistical difference was noted between the groups in terms of postoperative follow-up results. Conclusion: Bipolar TURP is a safe and highly effective technique which can be used in the surgical treatment of benign prostatic obstruction with minimal side effects. BIVAP saline vaporization of the prostate seems to be a potential alternative to bipolar TURP with shorter hospitalization time.